Standards and Export Decisions: Firm-Level Evidence from Developing Countries - Chen, Maggie Xiaoyang (2012)
Standards and technical regulations set in importing countries have become a rising concern to exporters, especially to those in developing countries. This paper examines the importance of various types of standards in developing-country firms' export decisions. Drawn from the World Bank Technical Barriers to Trade (TBT) Survey database, we find that different types of standards exhibit sharply distinct relations with firms' intensive and extensive margins of exports. Quality standards are positively correlated not only with firms' average export volume across markets and products but also their export scope, measured by the number of export markets and products. A similar relationship is found between labeling requirements and export scope. Certification procedures, however, are associated with a significant decline in the number of export markets and export products. Our results suggest that different approaches should be taken to address each type of technical regulations. Not all standards need to be negotiated away to boost trade, but negotiations on certification procedures with the aim of reaching Mutual Recognition Agreements (MRAs) can help firms improve economies of scale and scope.